Biodiversity knowledge and conceptions in Latin American: Towards an integrative new perspective for education research and practice - Bermudez, Gonzalo Miguel Angel (2022)
Biodiversity plays a crucial role in ecosystem functioning by providing essential benefits to people and improving their well-being, i.e., regulating material and non-material services; especially in cultural and natural rich landscapes, such as those found in Latin-American countries. Nevertheless, in spite of the utmost importance of sustaining human life, biodiversity is not only declining at unprecedented rates, but also this pervasive degradation has revealed both our mutual dependence and interconnectedness, with a profound need for a societal transformative change. To help meet this challenge, the aim of this work is to synthesise pertinent and state-of-the-art knowledge on biodiversity education by utilising a holistic approach and a Latin-American point of view, which will contribute towards understanding and targeting complex socio-ecological issues. The findings have unveiled an abundant number of studies in Latin American countries that have investigated the topic of teachers'and students'knowledge and their conceptions of biodiversity from both conventional scientific knowledge and interculturality. By promoting an integrative dialogue among these categories and their subcategories, several implications arose concerning scientists engaged in public outreach, environmental and sustainable development and science education researchers, those engaged in cultural studies, formal and non-formal education, and school teachers.